Corporate Social Responsibilities (CSR) themes from Bangladesh perspective - Rashed, al Karim (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my